A Study On Two Malaysian Isolates Of Infectious Bronchitis Virus - Arshad, Siti Suri (1993)

(untitled)
This research was carried out to investigate whether the outbreak of Infectious Bronchitis (18) in Malaysia is due to the vaccine virus or the emergence of a new serotype which is different from the vaccine strains. The study involves the comparison between the two local isolates (PJ41 and PJ43) and the three reference strains (H120 , H52 and M41 ) of Massachusetts derivative. Initial characterisation of the two isolates involved a study on their basic properties such as morphologies, hemagglutinating activity, pathogenicity in embryonated chicken eggs and their adaptibility in primary and secondary tissue cultures with the aid of Acridine Orange (AO ) , indirect immunoperoxidase ( lIP) and indirect immunofluorescent (IIF) staining (to compare localisation of the RNA) and the Hematoxylin and Eosin staining ( H&E) (to compare morphologic changes in cell culture ).Both isolates and reference strains revealed a corona-like appearance under electron microscopy and formed pathognomonic lesions of toe curling and dwarfing of the embryo. The virus strains were indistinguishable in their ability to produce cytopathic effects in both primary and secondary cell cultures. The AO staining indicated that the virus possesses a RNA . lIP and IIF tests indicated that they are located in the cytoplasm of the cell.The hemagglutinating activity however, showed that this activity is not always their properties when one of the isolates, (PJ43 ) , and one of the reference strains, ( H52) ' were unable to agglutinate erythrocytes.